A novel role for local immune suppression in chronic q fever infected abdominal aortic aneurysms?. (25th November 2020) - Staal, A.H.J; Cortenbach, K.R.G; Wever, P.C; Van Suylen, R.J; Poyck, P.P.C; Srinivas, M; Van Deuren, M; Bleeker-Rovers, M.C; Van Der Meer, J.W.M; De Vries, I.J.M; Van Kimmenade, R.R.J
Abstract: Background: Chronic Q fever (QCF) is the persistence of C. Burnettii after an acute infection. Atheromas in the abdominal aorta are a preferential location of this bacterial persistence and may result in accelerated abdominal aorta aneurysm (AAA) formation or even rupture. CQF is characterized by a poor response to antibiotic therapy with high mortality. The localization of the bacteria in the acidic lysosomes is thought to be the main cause of poor antibiotic efficacy. Purpose: A potent immune system is mandatory for successful antibiotic therapy. PBMC simulation assays have shown potent immune activation on stimulation with C. Burnettii. Here we assess whether this holds true in situ by combining 3 six-marker panels with phenotypical markers describing the adaptive and innate immune system and looking at key check-points in immune regulation. Methods: (Tissue) PCR-positive CQF infected AAAs (n=10) are compared to atherosclerotic AAAs (n=13) and normal abdominal aortas from kidney transplant donors (n=3). We combine DAPI and elastin autofluorescence with 3 distinct panels of 6 markers in an 8-color IHC technique (Vectra 3, Perkin Elmer, MA) to describe the local immune landscape. The panels focus on 1) adaptive immune response, 2) innate immune response and 3) checkpoint inhibitors. Cells were phenotyped and quantified using an automated quantitative analysis method. Results: In contrast to normal abdominal aortas, both atherosclerotic AAAs and CQF AAAs show impressive lymphocyte recruitment and proliferation with the formulation of very large tertiary lymphoid structures. CQF AAAs show a 2-fold increase in regulatory T cell numbers compared to atherosclerotic AAAs. These regulatory cells are both surrounding germinal centers and are seen throughout the tissue. Additionally, CQF AAAs show more positive cells and a higher expression of PD-L1, which is a key immunosuppressive mediator. Conclusion: The immune landscape within the aortic wall shows far greater immune suppression than previously found in in vitro and peripheral blood studies. We show that CQF infections are associated with severely increased numbers of regulatory T cells, even compared to the low-grade and chronic inflammation present in atherosclerosis. Subsequently, a look at the immune checkpoint PD-L1 shows an increased expression in CQF aortas, elucidating a possible underlying mechanism and treatment target. Funding Acknowledgement: Type of funding source: Public grant(s) – EU funding. Main funding source(s): ERC starting grant (ERC-2014-StG-336454-CoNQUeST); TTW-NWO open technology grant (STW-14716)